Towards Solving Baby Dumping In Malaysia By Using An Alternative: Baby Hatch - Azizah Abdul Majid; Tagaranao, Mariam Saidona; Yasmin Hanani Mohd. Safian; Termizi, Mazbah binti (Universiti Sains Islam Malaysia, 2024)
Baby dumping has become a serious phenomenon in Malaysia. The fact that newborn babies are dumped at the most inappropriate places such as toilets and junkyards is such a heinous crime. Despite various steps taken by the government and the society at large, the statistics of baby dumping is escalating. This should not happen in a country which upholds an image of a Muslim nation. This research will not only discuss the literature review with regards to the issue of baby dumping in Malaysia, but shall also provide an overview of an alternative solution to curb this problem which is known as the baby hatch. Opinions from the NGO (such as OrphanCARE Foundation) and the judiciary are referred to in order to find the best possible method to overcome baby dumping issue in Malaysia. This is an alternative to the legal procedure which falls under the Penal Code and other related Acts. Comparisons are needed to seek the best possible way for a solution of baby dumping and to understand the perceptions of the particularly well-informed segment of society on this alternative solution to baby dumping - baby hatch.